Historical review on the Comprehensive General Medicine specialty evolution in Cienfuegos - Rubén Darío García Núñez; María Aurelia San Juan Bosch; Carla María García San Juan (Medisur)
A review of the main events that occurred in the evolution of family medicine in Cuba and Cienfuegos is made. A search was carried out through the main databases available on the Infomed website. A valuable colleagues collaboration from different stages managed Public Health in the territory and the practical experience of the main author of the work is revealed, who has been absorbed in the origin and development of the specialty in the province, since its beginning to the present. The analysis of the events, published here, allows us to affirm that the family doctors of the Cienfuegos province, committed to the people, have to offer a comprehensive, continuous and quality medical service in each of the doctor´s offices, as well as the trainers of the new generations of health professionals guide each of the actions to achieve a professional, according to current social demands